2009
DOI: 10.1159/000209388
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) Polymerase Inhibition Down-Regulates Expression of Metastasis-Related Genes in CT26 Colon Carcinoma Cells

Abstract: Objectives: The current study was designed to test the hypothesis that inhibition of poly(ADP-ribose) polymerase in colorectal cancer mediates down-regulation of metastasis-related gene expression through the regulation of nuclear factor-κB (NF-κB) activity. Methods: Mouse colon carcinoma cells (CT26) were treated with and without the PARP inhibitor 5-aminoisoquinolin-1(2H)-one hydrochloride (5-AIQ). We investigated adhesion, migration and invasion of differently treated CT26 cells. In addition, the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 90 publications
1
23
0
Order By: Relevance
“…3c, d). This demonstrates diminished activation of NF-κB in PARG-shRNA cells resulting in decreased expression of its dependent genes [35][36][37][38] Silencing PARG Inhibits Metastasis of Colon Carcinoma MMP2 and MMP9 (Fig. 4c, d).…”
Section: Discussionmentioning
confidence: 97%
“…3c, d). This demonstrates diminished activation of NF-κB in PARG-shRNA cells resulting in decreased expression of its dependent genes [35][36][37][38] Silencing PARG Inhibits Metastasis of Colon Carcinoma MMP2 and MMP9 (Fig. 4c, d).…”
Section: Discussionmentioning
confidence: 97%
“…ABT-888 also potentiated radiation in HCT-116 colon carcinoma model [99] while, potent non-toxic PARP inhibitors used in LoVo human colon carcinoma cells showed excellent chemopotentiation for relevant anti tumor therapies [100]. Another PARP inhibitor, 5-Aminoisoquinolinone (5-AIQ) was found to prevent adhesion of HT-29 colonic cells to HUVEC [101] and in CT26 mouse adenocarcinoma cells it inhibited proliferation, migration of tumor cells, downregulated NF-K B as well as its expression genes in metastasis such as integrinβ1, MMP-2 and MMP-9 thus, putting forward its use in clinical trials [102]. Gallotannin (PARG inhibitor) used in CT26 colon carcinoma cell lines was found to suppress tumor growth factors [75].…”
Section: Parp and Parg Inhibitors In Experimental Trialsmentioning
confidence: 99%
“…Our previous studies had also showed that PARP-1 inhibition can dramatically decrease the activation of nuclear factor-kB and its DNA-binding activity (Li et al, 2009, Li et al, 2012. PARP-1 has been reported to be a co-activator of NF-kB in many inflammatory disorders (Pétrilli et al, 2004;Zheng et al, 2004).…”
Section: Discussionmentioning
confidence: 93%